Television narratives about ETA after the cessation of violence. Fiction, docuseries and documentary reports (2019-2020) - Mateos-Pérez, Javier (2024)
During the 2019-2020 season, six television programs about the terrorist organization ETA were broadcast in Spain. The aim of this research is to analyze the “television narrative” that has been constructed about ETA almost ten years after the cessation of violence. As the programs had different formats, a qualitative methodology based on textual analysis was used. The conclusions show a new narrative which recalled some historical facts and gave the victims a clearly prominent role. This resulted in a renewed discourse that builds collective memory in order to learn some lessons and move forward for the sake of coexistence and reconciliation.